Trial and error to mitigate the effects of the pandemic in Peru - Lorenzzi Bolaños, Aldo (2020)
This article first describes the events that occurred since the world was informed about the pandemic caused by COVID-19, and later how it spread throughout the world, reaching Peru with all the implications that the crisis has meant health care in our country will subsequently analyze the impacts on employment and companies, the stimuli and the measures taken by the government to mitigate the crisis caused by the pandemic.